2017
DOI: 10.7717/peerj.3082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of different vibration patterns to guide blind people

Abstract: The literature indicates the best vibration positions and frequencies on the human body where tactile information is transmitted. However, there is a lack of knowledge about how to combine tactile stimuli for navigation. The aim of this study is to compare different vibration patterns outputted to blind people and to determine the most intuitive vibration patterns to indicate direction for navigation purposes through a tactile belt. The vibration patterns that stimulate the front side of the waist are preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, this study was limited to testing four obvious directions: front, back, left, and right, which might have resulted in better performance of the system. Other studies [50,51,52] demonstrated the capability of a system with eight vibration motors equally spaced around the waist, for assisting the navigation of visually impaired people. Marston et al [53,54] demonstrated the applicability of a vibrotactile system wearable on the wrist to assist navigation of visually impaired individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study was limited to testing four obvious directions: front, back, left, and right, which might have resulted in better performance of the system. Other studies [50,51,52] demonstrated the capability of a system with eight vibration motors equally spaced around the waist, for assisting the navigation of visually impaired people. Marston et al [53,54] demonstrated the applicability of a vibrotactile system wearable on the wrist to assist navigation of visually impaired individuals.…”
Section: Introductionmentioning
confidence: 99%
“…While observing the interface of vibration motors used in the previously discussed navigation assistance systems, it was found that most of these studies [44,45,48,49,50,51,52] had their motors arranged around a waist belt at an equal spacing to assist in navigation. Few studies [56,57] used a 3 × 3 back-array arrangement of motors on the back of people to guide in navigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orcam). However, only few studies have been done to test their effectiveness for people with visual impairments [41][42][43][44][45]. None of the mentioned applications were used by the participants in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there have been many developments applying different sensors, such as sonar, infrared, optical, and GPS. Additionally, the auditory [28,[30][31][32] and tactile [21,[33][34][35][36][37][38][39][40][41][42][43][44] modalities have been used to support PVIs to improve the ability of PVIs to navigate independently [10,29,45,46]. Despite these developments, only few of these systems have been commercialized and are widely used in the everyday life of PVIs [46].…”
Section: Navigationmentioning
confidence: 99%